Pengaruh tinggi kolom pada distilasi terhadap kadarbioetanol dari tebu (Saccharum officinarum) (Effect of column height on distillation on bioethanol levels from sugarcane (Saccharum officinarum) - Mely Afriani; - Gusnedi; - Ratnawulan (PILLAR OF PHYSICS, 2015)
Bioetanol is the altenative fuel from raw material plant that contains carbohydrate which is the sugarcane plant. The making of biooetanol from sugarcane plant done by the process of distillation. The process of distillation is how separation of liquid from its alloy based on difference in boiling point or based on the ability of a substance to evaporate. The process of distillation unit is referred to as a distillation column. Distillation columns can separate between ethanol and water. The research aims to know the influence of high columns against the resulting bioetanol levels on sugarcane juice. Result on measurement levels bioetanol for each variation of the height of the column is obtained as follows: for the column height of 0 (No column) there are levels of 35%, for the column height of 0,5 metres there are levels of 75%, for the column height of 1 metre there are levels of 86%, and for the column height of 2 metre there are levels of 87%. In this research founded high distillation column influence against the increasingly high levels of bioetanol distillation column which then levels will be higher because bioetanol in column a different pressure loss occurs and the rate of ethanol vapor